Self-reported physical activity within and outside the neighborhood: Criterion-related validity of the Neighborhood Physical Activity Questionnaire in German older adults. Issue 1 (2nd January 2018) - Bödeker, Malte; Bucksch, Jens; Wallmann-Sperlich, Birgit
ABSTRACT: The Neighborhood Physical Activity Questionnaire allows to assess physical activity within and outside the neighborhood. Study objectives were to examine the criterion-related validity and health/functioning associations of Neighborhood Physical Activity Questionnaire-derived physical activity in German older adults. A total of 107 adults aged ≥60 years completed the Neighborhood Physical Activity Questionnaire and Short Form 12 Health Survey. A subsample of 58 participants wore piezoelectric pedometers for 7 consecutive days. Rank correlation coefficients (ρ) along with 95% confidence intervals (CIs) were computed for the criterion-related validity and health/functioning associations of single Neighborhood Physical Activity Questionnaire modules and total physical activity. Criterion-related validity was moderate (ρ ≤ .60) for total physical activity, total walking, and neighborhood walking, but low (ρ ≤ .40) for walking outside the neighborhood. Health/functioning associations were moderate for recreation walking and low for total physical activity, total walking, and walking within as well as outside the neighborhood. The study provides low-to-moderate validity evidence of Neighborhood Physical Activity Questionnaire-derived physical activity in older adults.